PENGARUH HARD SKILL, SOFT SKILL, DAN SELF-EFFICACY TERHADAP KESIAPAN KERJA PADA MAHASISWA TINGKAT AKHIR UNIVERSITAS MUHAMMADIYAH MAKASSAR - Atiqa R, Nurul; Aisyah, Siti; Nasrullah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is grounded in the growing importance of work readiness among final-year students in responding to increasingly complex and competitive labor market demands. Work readiness is not solely determined by technical competencies but is also shaped by non-technical abilities and individual psychological factors. Accordingly, this research aims to examine the influence of hard skills, soft skills, and self-efficacy on the work readiness of final-year students in the Management Study Program at Universitas Muhammadiyah Makassar. The study draws upon Human Capital Theory, which emphasizes skill development as an essential investment in human resources, as well as the concept of self-efficacy, which relates to an individual's belief in their capacity to face challenges. A quantitative approach was employed, utilizing multiple linear regression analysis. Data were collected through questionnaires distributed to 79 respondents, selected using purposive sampling techniques. The findings indicate that, partially, hard skills have a positive but statistically insignificant effect on work readiness. In contrast, soft skills and self-efficacy demonstrate a positive and significant influence. Simultaneously, the three independent variables collectively contribute substantially to work readiness, as reflected by a coefficient of determination of 57.7%. In conclusion, the study reveals that students' work readiness is more strongly influenced by soft skills and self-efficacy than by hard skills. These findings suggest that strengthening interpersonal competencies and fostering confidence are critical components in preparing students for successful entry into the workforce.